Heat Shock Proteins Regulate Activation-induced Proteasomal Degradation of the Mature Phosphorylated Form of Protein Kinase C - Lum, Michelle A. (American Society for Biochemistry and Molecular Biology, 2013)
Although alterations in stimulus-induced degradation of PKC have been implicated in disease, mechanistic understanding of this process remains limited. Evidence supports the existence of both proteasomal and lysosomal mechanisms of PKC processing. An established pathway involves rate-limiting priming site dephosphorylation of the activated enzyme and proteasomal clearance of the dephosphorylated protein. However, here we show that agonists promote down-regulation of endogenous PKCα with minimal accumulation of a nonphosphorylated species in multiple cell types. Furthermore, proteasome and lysosome inhibitors predominantly protect fully phosphorylated PKCα, pointing to this form as a substrate for degradation. Failure to detect substantive dephosphorylation of activated PKCα was not due to rephosphorylation because inhibition of Hsp70/Hsc70, which is required for re-priming, had only a minor effect on agonist-induced accumulation of nonphosphorylated protein. Thus, PKC degradation can occur in the absence of dephosphorylation. Further analysis revealed novel functions for Hsp70/Hsc70 and Hsp90 in the control of agonist-induced PKCα processing. These chaperones help to maintain phosphorylation of activated PKCα but have opposing effects on degradation of the phosphorylated protein; Hsp90 is protective, whereas Hsp70/Hsc70 activity is required for proteasomal processing of this species. Notably, down-regulation of nonphosphorylated PKCα shows little Hsp70/Hsc70 dependence, arguing that phosphorylated and nonphosphorylated species are differentially targeted for proteasomal degradation. Finally, lysosomal processing of activated PKCα is not regulated by phosphorylation or Hsps. Collectively, these data demonstrate that phosphorylated PKCα is a direct target for agonist-induced proteasomal degradation via an Hsp-regulated mechanism, and highlight the existence of a novel pathway of PKC desensitization in cells.